Optimisation deep drawing process parameters using FE simulation - Katimon, Mohd Nizam (2008)
This paper presents the modeling simulation and experimental validation of cylindrical cup deep drawing. Prediction of the deep drawing results which includes determination of the optimum Blank Holder Force (BHF) and the thickness distribution of the sheet metal (blank) will decrease the production cost and time. Before performing the Finite Element (FE) analysis, it is required to understand the sheet metal (blank) properties and material model. In this FE analysis, the effect of fixed BHF on the cylindrical cup wall thickness distribution is examined. According to the experimental study, the optimum and maximum values of fixed BHF was at 1 kN and 11 kN respectively. These values are determined without the blank exceeding the tearing limits. Comparison of simulation and experimental study indicates that the FE model is considered valid, which can be seen from the similar thickness profile of simulation and experimental results.